Rosuvastatin Induces Renal HO-1 Activity and Expression Levels as a Main Protective Mechanism against STZ-Induced Diabetic Nephropathy - Gehan H. Heeba; Marwa A. M. Ali; Azza A. K. El-Sheikh (Medicina, 2022)
Background and Objectives: Nephroprotective effect of statins is still controversial. The aim of this study was to investigate the possible hemin-like nephroprotective effect of rosuvastatin (RSV) in streptozotocin (STZ)-induced diabetic rats. Materials and Methods: DN was induced in rats via a single dose of 50 mg/kg STZ i.p., with or without RSV (10 mg/kg orally) for 30 days. To investigate hemin-like effect of RSV on renal heme oxygenase-1 (HO-1), RSV was administered in the presence or absence of an inhibitor of HO-1; zinc protoporphyrin-XI (ZnPP), in a dose of 50 µmol/kg i.p. Results: Induction of diabetes with STZ caused, as expected, significant hyperglycemia, as well as deteriorated kidney function, lipid profile and histopathological architecture. The DN group also showed renal oxidative stress, indicated by decreased superoxide dismutase, catalase, and reduced glutathione, with increased malondialdehyde, myeloperoxidase and nitric oxide. Renal expression of inflammatory marker TNF-α, and pro-apoptotic marker caspase 3, were also increased in the DN group. Administration of RSV in DN rats did not improve glucose level but succeeded in recovering kidney function and normal structure as well as improving the lipid profile. RSV also improved renal oxidative, inflammatory, and apoptotic statuses. Interestingly, the administration of RSV increased renal expression and activity of HO-1 compared to the untreated DN group. Co-administration of ZnPP blocked the effect of RSV on HO-1 and deteriorated all RSV favorable effects. Conclusions: RSV can protect against DN, at least in part, via increasing renal HO-1 expression and/or activity, which seems to be upstream to RSV antioxidant, anti-inflammatory, and anti-apoptotic effects.